Sonic Hedgehog receptor Patched deficiency in astrocytes enhances glucose metabolism in mice - Linda Tirou; Mariagiovanna Russo; Helene Faure; Giuliana Pellegrino; Clement Demongin; Mathieu Daynac; Ariane Sharif; Jeremy Amosse; Soazig Le Lay; Raphaël Denis; Serge Luquet; Mohammed Taouis; et al. (Elsevier, 2021)
Objective: Astrocytes are glial cells proposed as the main Sonic hedgehog (Shh)-responsive cells in the adult brain. Their roles in mediating Shh functions are still poorly understood. In the hypothalamus, astrocytes support neuronal circuits implicated in the regulation of energy metabolism. In this study, we investigated the impact of genetic activation of Shh signaling on hypothalamic astrocytes and characterized its effects on energy metabolism. Methods: We analyzed the distribution of gene transcripts of the Shh pathway (Ptc, Gli1, Gli2, and Gli3) in astrocytes using single molecule fluorescence in situ hybridization combined with immunohistofluorescence of Shh peptides by Western blotting in the adult mouse hypothalamus. Based on the metabolic phenotype, we characterized Glast-CreERT2-YFP-Ptc−/− (YFP-Ptc−/−) mice and their controls over time and under a high-fat diet (HFD) to investigate the potential effects of conditional astrocytic deletion of the Shh receptor Patched (Ptc) on metabolic efficiency, insulin sensitivity, and systemic glucose metabolism. Molecular and biochemical assays were used to analyze the alteration of key pathways modulating energy metabolism, insulin sensitivity, glucose uptake, and inflammation. Primary astrocyte cultures were used to evaluate a potential role of Shh signaling in astrocytic glucose uptake. Results: Shh peptides were the highest in the hypothalamic extracts of adult mice and a large population of hypothalamic astrocytes expressed Ptc and Gli1-3 mRNAs. Characterization of Shh signaling after conditional Ptc deletion in the YFP-Ptc−/− mice revealed heterogeneity in hypothalamic astrocyte populations. Interestingly, activation of Shh signaling in Glast+ astrocytes enhanced insulin responsiveness as evidenced by glucose and insulin tolerance tests. This effect was maintained over time and associated with lower blood insulin levels and also observed under a HFD. The YFP-Ptc−/− mice exhibited a lean phenotype with the absence of body weight gain and a marked reduction of white and brown adipose tissues accompanied by increased whole-body fatty acid oxidation. In contrast, food intake, locomotor activity, and body temperature were not altered. At the cellular level, Ptc deletion did not affect glucose uptake in primary astrocyte cultures. In the hypothalamus, activation of the astrocytic Shh pathway was associated with the upregulation of transcripts coding for the insulin receptor and liver kinase B1 (LKB1) after 4 weeks and the glucose transporter GLUT-4 after 32 weeks. Conclusions: Here, we define hypothalamic Shh action on astrocytes as a novel master regulator of energy metabolism. In the hypothalamus, astrocytic Shh signaling could be critically involved in preventing both aging- and obesity-related metabolic disorders.